2018
DOI: 10.1080/20477724.2017.1422615
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of dihydrofolate reductase gene mutations inPlasmodium falciparumparasites among pregnant women in Nigeria after reported use of sulfadoxine-pyrimethamine

Abstract: This study assesses the prevalence of asymptomatic Plasmodium falciparum parasitemia positivity and P. falciparum dihydrofolate reductase (pfdhfr) mutations in parasite isolates among pregnant women in Southwest Nigeria. Plasmodium falciparum parasitemia was confirmed by microscopy and nested PCR in 200 pregnant women attending antenatal care. The prevalence of pfdhfr polymorphisms was determined by direct sequencing of the gene fragments containing the C50R, N51I, C59R, S108N, and I164L mutations. Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The SP doses have not reduced the MOI. This might result from the carriage of SP-resistant parasites in such women as suggested earlier (Moussiliou et al, 2013, Koukouikila-Koussounda et al, 2015Ojurongbe et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…The SP doses have not reduced the MOI. This might result from the carriage of SP-resistant parasites in such women as suggested earlier (Moussiliou et al, 2013, Koukouikila-Koussounda et al, 2015Ojurongbe et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…Similar findings have been reported in Nigeria and other countries across SSA [ 17 , 53 ]. This suggests that the quadruple mutations are already fixed in these populations [ 18 , 32 , 54 ]. Indications from other studies however revealed that the protective effect of SP-IPTp remains intact, regardless of the high prevalence of this quadruple Pfdhfr - Pfdhps mutant [ 2 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Nigeria to determine the prevalence of positive asymptomatic Plasmodium falciparum parasitemia amongst pregnant women, it was reported that 30% (60/200) of the recruited women has asymptomatic P. falciparum infection [32]. Malaria susceptibility rises throughout pregnancy, making pregnant women a major parasite reserve in the population.…”
Section: Epidemiology Of Severe Malaria In Pregnancymentioning
confidence: 99%
“…In south western Nigeria, dhfr (S108N), and dhps (K540E) resistant genes of plasmodium parasite have been observed among isolates from children, pregnant women and other adult cohorts [63]. Another report in Nigeria recorded a very high frequency of the Plasmodium falciparum dhfr triple-mutant alleles (N51I, C59R, and S108N) at 63% (38/60) while none of the isolates carried the I164L mutation [32]. In another study, the frequency of mutations at S436A, A437G, A581G and A613S positions in dhps gene of plasmodium parasite was 82.1% (23/28), 96.4% (27/28), 71.4% (20/28) and 71.4% (20/28) respectively having reported in the same study that the triple mutations in dhfr gene was almost fixed; S108N (100%), N51I (93%) and C59R (93%) [64].…”
Section: Drug Resistancementioning
confidence: 99%